COMPUTERIZED SYSTEMS USED TO QUANTIFY THE SUCCESS OF THE PROSTHETIC TREATMENT - Cosmin-Ionuţ Creţu; Murariu Alice; Vasluianu Roxana; Dascălu Cristina; Agop-Forna Doriana (Romanian Dental Association for Education, 2019)
Introduction: The new methodology of using expert systems forces the clinician to make a decision based on both his own knowledge and the expert system. The advantage of using expert system would be the ability of these systems to make an analysis of the patient's data more accurate than the one made solely on the basis of human reasoning. Materials and Methods: The study was conducted on a batch of 47 patients diagnosed with partially edentulous, subtotal edentulous, or total edentulous in at least one jaw. The patients underwent clinical and paraclinical examinations. Using the PRODENT application platform, an expert system was developed for assessing the clinical cases and providing a therapeutic solution with a certain degree of plausibility. Results: Using PRODENT software, we have found the following initial scores S1: favorable type A 40%, medium type B 30% and clinically unfavorable type C 30%. Concerning the S2 score, the best therapeutic choice was present in 50% cases, the unfavorable therapeutic solution in 30% and the intermediate treatment in 20% of the cases. Conclusions: The results show the need for an algorithm that combines conventional methods with computerized methods in the investigation of complex oral rehabilitation cases.